2018
DOI: 10.1038/s41598-018-34594-2
|View full text |Cite
|
Sign up to set email alerts
|

An Electroencephalography Bioassay for Preclinical Testing of Analgesic Efficacy

Abstract: We present a multimodal method combining quantitative electroencephalography (EEG), behavior and pharmacology for pre-clinical screening of analgesic efficacy in vivo. The method consists of an objective and non-invasive approach for realtime assessment of spontaneous nociceptive states based on EEG recordings of theta power over primary somatosensory cortex in awake rats. Three drugs were chosen: (1) pregabalin, a CNS-acting calcium channel inhibitor; (2) EMA 401, a PNS-acting angiotensin II type 2 receptor i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(24 citation statements)
references
References 58 publications
0
24
0
Order By: Relevance
“…2a, left panel), paw withdrawal threshold in the hind paw ipsilateral to CCI decreased significantly to 5.93 ± 0.76 g compared to baseline 11.58 ± 0.54 g (p = 0.0002, n = 8 rats), suggesting successful reproduction of the model. Previous studies from our laboratory demonstrated that spontaneous pain in rats following CCI correlates reliably with enhanced EEG theta (4-8 Hz) power in the contralateral S1 21,23,24 . In this study, results also suggest ( Fig.…”
Section: Model Validation Chronic Constriction Injury (Cci)mentioning
confidence: 77%
See 2 more Smart Citations
“…2a, left panel), paw withdrawal threshold in the hind paw ipsilateral to CCI decreased significantly to 5.93 ± 0.76 g compared to baseline 11.58 ± 0.54 g (p = 0.0002, n = 8 rats), suggesting successful reproduction of the model. Previous studies from our laboratory demonstrated that spontaneous pain in rats following CCI correlates reliably with enhanced EEG theta (4-8 Hz) power in the contralateral S1 21,23,24 . In this study, results also suggest ( Fig.…”
Section: Model Validation Chronic Constriction Injury (Cci)mentioning
confidence: 77%
“…EEG implant. As described previously 23,24,46 , the head was fixed in a stereotaxic apparatus, and the skull was exposed after a small midline skin incision. A stainless-steel screw electrode (0-80 ga 1/8-inch, impedance = 0.6 www.nature.com/scientificreports/ Ω; component Supply Company, Fort Meade, FL) was placed over the intact skull (i.e.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…However most behavioural or even imagery paradigms (i.e. grimace scales, conditioned place preference, burrowing, brain imaging) proposed lately may be too subjective or lack the necessary temporal resolution to respond to these criteria [3].…”
Section: Introductionmentioning
confidence: 99%
“…Here we have asked whether pain perception might be encoded through different physiological signals and we sought to assess their possible interactions. The physiological response to pain has been addressed previously using approaches like EEG [6], [7] and PPG [8], [9], yet these signals are typically analyzed separately. Moreover, the paradigm to produce painful stimulation relies on human intervention [10] or environmental factors [11], which may compromise the reliability of these results.…”
Section: Introductionmentioning
confidence: 99%